Effect of Vitamin E Supplementation in the Low Density Lipoprotein Consentration and Histopatologic Changes of the Wistar Rats Aorta Given High Fat Diet - Razali Daud (Universitas Syiah Kuala, 2014)
The aims of this research were: a) to determine the protective effect of vitamin E in the low density lipoprotein concentration and aorta , b) to give information, especially in the relationship between the high fat diet and the incidence of cardiovascular diseases. Twenty five male wistarrats weighing 200–250 grams at the age of 3 months were used in this study. Completely randomized design was implemented for thisexperiment. The rats were acclimated for a week and fed with CP 521 (basal). The rats were then randomly allotted into 5 groups, 5 sampleseach. The rats were fed basal (CP 521) as control (G I), high fat diet (CP 521 + palm oil 10%) + 50 IU vitamin E (G II), high fat diet fat + 100IU vitamin E (G III), high fat diet + 200 IU vitamin E (G IV) and high fat diet + 400 IU vitamin E (G V). Diets were given about 10% of bodyweigh and it’s fed up every day. Water was given ad libitum. Based on statistically analysis showed that very significance (P0,01) between thetreatment. Result indicated that given high fat diet + 400 IU vitamin E could apparently reduce LDL concentration, Lesion in the aortaconsisting of hemorrhagic and hyperemic were found in all rats receiving high fat diet supplemented with less than 400 IU vitamin E. The ratsreceiving high fat diet + 400 IU vitamin E (G V) the aorta were normal. It was concluded that the diet containing high fat and high vitamin Esupplementation (400 IU ration) in the diet could protected the incidence of atherosclerosis.____________________________________________________________________________________________________________________Key words: atherosclerosis, high fat diet, vitamin E,